Effect of tranexamic acid on coagulation and fibrinolysis in women with postpartum haemorrhage (WOMAN-ETAC): protocol and statistical analysis plan for a randomized controlled trial (2016)
Background: Postpartum haemorrhage (PPH) is a leading cause of maternal death. Tranexamic acid has the potential to reduce bleeding and a large randomized controlled trial of its effect on maternal health outcomes in women with PPH (The WOMAN trial) is ongoing. We will examine the effect oftranexamic acid on fibrinolysis and coagulation in a subset of WOMAN trial participants. Methods: Adult women with clinically diagnosed primary PPH after vaginal or caesarean delivery are eligible for inclusion in the WOMAN trial. In a sub-group of trial participants, blood samples will be collected at baseline and 30 minutes after the first dose of tranexamic acid or matching placebo. Our primary objective is to evaluate the effect of tranexamic acid on fibrinolysis. Fibrinolysis will be assessed by measuring D-dimers and by rotational thromboelastometry (ROTEM). Secondary outcomes are international normalized ratio (INR), prothrombin time (PT), activated partial thromboplastin time (APTT), fibrinogen, haemoglobin and platelets. We aim to include about 180 women from the University College Hospital, Ibadan in Nigeria. Discussion: This sub-study of WOMAN trial participants should provide information on the mechanism of action of tranexamic acid in women with postpartum haemorrhage. We present the trial protocol and statistical analysis plan. The trial protocol was registered prior to the start of patient recruitment. The statistical analysis plan was completed before un-blinding.